CSC776: Emergent Computing Technologies / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
This course will explore current emergent computing technologies globally and locally to keep the students abreast with the opportunities created by these emergent technologies. Based on research papers, industry reports, talks and visits, students will be required to explore the emerging computing technologies body of knowledge, analyse and appraise them. This course also provides the opportunity for students to relate emerging computing technologies, their significance, the impact on society, and values, as well as a platform to sharpen their leadership and teamwork skills. It will explore different current emerging computing technologies including the Internet of Things, cloud computing, mobile computing, networks, end user computing, big data and analytics. This course will cover emergent computing technologies such as those outline below, but the list of actual technologies covered may change as the technologies progress, in terms of both additions and deletions of technologies. The course will be based mostly on the most recent research papers on emerging computing technologies and thus the detailed course contents may and will change accordingly.